The emergence of clause construction in children who use speech generating devices. (3rd April 2019) - Savaldi-Harussi, Gat; Lustigman, Lyle; Soto, Gloria
Abstract: This study aimed to detect patterns in clause construction structural changes produced by four participants aged 9;5–13;7 (years;months) with motor speech disorders who used speech-generating devices. Sequences of adult–child interactions, drawn from the data of a larger study focused on enhancing vocabulary and grammar skills, were examined. This current study comprises a secondary analysis of a corpus of 29 conversations totalling 808.36 min, analysing clause structures by type, linguistic complexity, and intensity of adult prompts (number of turns). Results show that, over time, the participants' clause structure complexity increased through addition of phrase-internal elements such as inflections, articles, and prepositions. Use of specific grammatical elements followed the developmental stages observed in children with typical development. For all participants, the personal pronoun I (first-person singular) emerged before she, he (third-person singular), and we or they (plural). Participants with the highest number of adult–child co-constructed clauses also had the highest number of well-formed clauses. The intensity of adult prompts increased as clause structures became more complex and as participants needed more support. Implications for practice and theory are discussed.